'The community comes to life': How Social Grants Enable Participation in the Local Economy and Possible Effect on Post-COVID-19 Economic Recovery in Soweto South Africa. Issue 3 (2nd September 2022) - Nnaeme, Chibuikem Charles
Abstract : South Africa has an extensive social grant program reaching over 45 percent of the population and which has mitigated high poverty in the post-apartheid epoch. Yet the impacts on urban poor community economic activities are yet to be duly appreciated. As the major capital injection into the local economy amidst a high rate of poverty and unemployment, the fund serves as the catalyst that enables both beneficiaries and non-beneficiaries to participate in economic activities. A qualitative study was carried out in Soweto to explore linkages between social grants and participation in local economic activities. The findings show a strong nexus between social grants and participation in local economic activities. The key relevance of this study rests on its evidence-based suggestion of the positive impact of social grants on post-COVID-19 economic recovery, especially in poor urban communities such as Soweto.